2022
DOI: 10.3390/jrfm15020056
|View full text |Cite
|
Sign up to set email alerts
|

Eurozone Stock Market Reaction to Monetary Policy Interventions and Other Covariates

Abstract: The joint effect of the global economic and sovereign debt crisis forced the European Central Bank (ECB) to apply conventional and non-standard expansionary monetary policy interventions in order to stabilize eurozone economies. We conducted a panel regression econometric analysis to study the influence of euro area monetary authority policy interventions, along with two main macroeconomic variables and a sentiment indicator, on market equity returns of eurozone countries for the period January 2007 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Additionally, the multivariate DCC-GARCH model effectively identifies cross-market volatility transmissions, thereby advancing our understanding of cryptocurrency dynamics and contributing valuable insights to the financial economics literature through the application of advanced econometric models (Li et al 2021;Liu and Ouyang 2014). Petrakis et al (2022) demonstrate that conventional and unconventional monetary interventions positively impacted equity returns, especially in less affected core eurozone nations. The study found a negative correlation between inflation and market returns, while industrial production positively influenced market gains.…”
Section: Inter-market Transmissions Dynamicsmentioning
confidence: 99%
“…Additionally, the multivariate DCC-GARCH model effectively identifies cross-market volatility transmissions, thereby advancing our understanding of cryptocurrency dynamics and contributing valuable insights to the financial economics literature through the application of advanced econometric models (Li et al 2021;Liu and Ouyang 2014). Petrakis et al (2022) demonstrate that conventional and unconventional monetary interventions positively impacted equity returns, especially in less affected core eurozone nations. The study found a negative correlation between inflation and market returns, while industrial production positively influenced market gains.…”
Section: Inter-market Transmissions Dynamicsmentioning
confidence: 99%
“…The interest rate channel denotes that a conventional policy influences the present value of future net cash flows, which affects equity prices (Petrakis et al 2022). Cutting interest rates decreases the risk-free rate, which is used as a discounting factor and so decreases the risk premium of equities, boosting cash flows projected (Petrakis et al 2022).…”
Section: The Effect Of Interest Rates On the Equity Marketmentioning
confidence: 99%
“…The interest rate channel denotes that a conventional policy influences the present value of future net cash flows, which affects equity prices (Petrakis et al 2022). Cutting interest rates decreases the risk-free rate, which is used as a discounting factor and so decreases the risk premium of equities, boosting cash flows projected (Petrakis et al 2022). On the contrary, when interest rates and firms' financing costs rise, investors will reduce their stock and choose other financial assets, resulting in a fall in share prices (Gu et al 2021).…”
Section: The Effect Of Interest Rates On the Equity Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying dynamics of unconventional policies as well as most financial markets such as stock markets are significantly complex [ 13 , 37 ]. Considering the Euro area, Petrakis [ 38 ] confirmed that both CMP and UMP have a positive lagged impact on euro equity market returns. The findings showed that market indices are mainly affected by a cut in interest rates.…”
Section: Introductionmentioning
confidence: 99%